2019
DOI: 10.3390/antiox8100431
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Intensity Resistive Training Reduces Oxidative Stress and Improves Muscle Mass and Function in Older Individuals

Abstract: An innovative moderate-intensity resistive exercise-training (RT) program was tested in thirty-five sarcopenic elders (SAR). The subjects were randomized into two groups: SAR training (SAR-RT), n = 20, 73.0 ± 5.5 years, or SAR non-training (SAR-NT), n = 15, 71.7 ± 3.4 years. The training consisted of 12-week progressive RT, thrice/week, at 60% one-repetition maximum (1RM), 3 sets, 14–16 repetitions for both upper and lower limbs. The pre and post intervention measurements included: the skeletal muscle index (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 56 publications
2
46
0
1
Order By: Relevance
“…Previous studies have shown that DRT is indicated for the treatment of loss of function and sarcopenia [27,28], and to reduce muscle oxidative stress [28]. In line with previous reports [28,32], the positive changes in the muscular redox balance in response to DRT may come about due to a decrease in the production of ROS. This reduced ROS production may be secondary to the improvement in antioxidant defense as evidenced by the reduction of prooxidant markers (TBARS and GSSG) and an increase in antioxidants (trolox equivalent, CAT, and lower GSSG/GSH ratio).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Previous studies have shown that DRT is indicated for the treatment of loss of function and sarcopenia [27,28], and to reduce muscle oxidative stress [28]. In line with previous reports [28,32], the positive changes in the muscular redox balance in response to DRT may come about due to a decrease in the production of ROS. This reduced ROS production may be secondary to the improvement in antioxidant defense as evidenced by the reduction of prooxidant markers (TBARS and GSSG) and an increase in antioxidants (trolox equivalent, CAT, and lower GSSG/GSH ratio).…”
Section: Discussionsupporting
confidence: 64%
“…The hypothesis that DRT would be superior to IRT in altering aging biomarkers was confirmed. Several training models like aerobic training, DRT, and IRT have been investigated to determine efficacy in mitigating the effects of aging [21,23,[27][28][29]31]. Data from the current intervention suggest that DRT reduced the mRNA of p53 and shelterin (Trf1, Trf2, and Xrcc5) independently of Chk2 after 16 weeks of training.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Vezzoli et al concluded that 12 weeks of moderate-intensity resistance training can minimize the generation of ROS and oxidative stress. They stated that moderate-intensity resistance training can overcome anabolic resistance and maximize protein synthesis in older adults [ 81 ]. In the case of acute resistance exercise, Motameni et al showed that three types of resistance exercise (hypertrophy, strength, and power) did not worsen oxidative stress in women who practiced resistance exercise.…”
Section: The Influence Of the Physical Exercise On Oxidative Stresmentioning
confidence: 99%